1999
DOI: 10.1094/pdis.1999.83.10.931
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of High Resistance to Rice Yellow Mottle Virus (RYMV) in Cultivars of Two Cultivated Rice Species

Abstract: Ndjiondjop, M. N., Albar, L., Fargette, D., Fauquet, C., and Ghesquière, A. 1999. The genetic basis of high resistance to rice yellow mottle virus (RYMV) in cultivars of two cultivated rice species. Plant Dis. 83:931-935.Three cultivars of Oryza sativa (IR64, Azucena, and Gigante) and four cultivars of O. glaberrima (Tog5681, Tog5673, CG14, and SG329) were evaluated for their resistance to two isolates of rice yellow mottle virus (RYMV) by enzyme-linked immunosorbent assay (ELISA) and symptomatology. Cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 16 publications
2
73
0
1
Order By: Relevance
“…Since this species is inherently low yielding compared to O. sativa, its cultivation area has decreased (Linares, 2002). However, O. glaberrima can be a source of resistance to various indigenous biotic constraints such as rice yellow mottle virus (Abo et al, 1998;Ndjiondjop et al, 1999Ndjiondjop et al, , 2001Deless et al, 2010;Maji et al, 2010), African rice gall midge Williams et al, 1999;Nwilene et al, 2009), weeds Dingkuhn et al, 1999;Fofana and Rauber, 2000), and nematodes (Coyne et al, 1995Plowright et al, 1999;Soriano et al, 1999;Lorieux et al, 2003), and to abiotic stresses such as drought (Jones et al, 1997a(Jones et al, , 1997bMaji et al, 2010;Ndjiondjop et al, 2010), submergence (Futakuchi et al, 2001;Kawano et al, 2008), iron toxicity (Sahrawat and Sika, 2002) and low phosphorus availability in acid soils (Tobita et al, 2003). Thus, this species is highly adaptable to the local rice cultivation conditions in Africa.…”
Section: Origin Of Oryza Glaberrima and Its Role In Rice Breedingmentioning
confidence: 99%
“…Since this species is inherently low yielding compared to O. sativa, its cultivation area has decreased (Linares, 2002). However, O. glaberrima can be a source of resistance to various indigenous biotic constraints such as rice yellow mottle virus (Abo et al, 1998;Ndjiondjop et al, 1999Ndjiondjop et al, , 2001Deless et al, 2010;Maji et al, 2010), African rice gall midge Williams et al, 1999;Nwilene et al, 2009), weeds Dingkuhn et al, 1999;Fofana and Rauber, 2000), and nematodes (Coyne et al, 1995Plowright et al, 1999;Soriano et al, 1999;Lorieux et al, 2003), and to abiotic stresses such as drought (Jones et al, 1997a(Jones et al, , 1997bMaji et al, 2010;Ndjiondjop et al, 2010), submergence (Futakuchi et al, 2001;Kawano et al, 2008), iron toxicity (Sahrawat and Sika, 2002) and low phosphorus availability in acid soils (Tobita et al, 2003). Thus, this species is highly adaptable to the local rice cultivation conditions in Africa.…”
Section: Origin Of Oryza Glaberrima and Its Role In Rice Breedingmentioning
confidence: 99%
“…Insect vector control and prophylactic measures such as high surveillance of seedbeds, fields and weed reservoirs are also used for management of RYMV despite time-consuming and variable efficiency [1] [2]. The resistance of rice plants to RYMV is controlled by the recessive gene RYMV1 [3], located on chromosome 4 [4] and encodes the isoform of the eukaryotic translation initiation factor 4G (eIF (iso) 4G1) [5] but RYMV is able to evolve fast. Generally, most of resistance sources to RYMV obtained from Oryza glaberrima.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most of resistance sources to RYMV obtained from Oryza glaberrima. Several highly resistant varieties with known genes of resistant to RYMV have been identified that include rice cultivars Gigante (rymv1-2) [3], Tog12387 (rymv1-3) [6], Tog5681 (rymv1-3) [4], Tog5438 (rymv1.4), Tog5672 (rymv1-4+rymv2) and Tog5674 (rymv1-5) [7]. Resistance conferred by RYMV2 and RYMV3 genes have currently been identified on Oryza glaberrima Tog7291 and Tog5307, respectively [2] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Azucena and a few other cultivars of Oryza sativa subsp. japonica (Ndjiondjop et al 1999). High resistance is conferred by a single recessive gene Rymv 1 which has been identified in the rice cv.…”
mentioning
confidence: 99%